PENGAJARAN SASTRA DI MADRASAH IBTIDAIYYAH - Eka Putra (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2021)
Literature as a lesson in school is material that has an important role to trigger the creativity of students. The reason is that literature has a human side that can add insight and knowledge to readers. Mechanically, the teaching of literature in schools can achieve three main learning abilities, namely affective abilities, cognitive abilities, and psychomotor abilities. Ability is a basic human ability that is related to one's emotions. Cognitive abilities are abilities possessed by humans based on thought. Psychomotor ability is the ability to manage the psychological side to survive various problems. The implementation, literature and language learning is carried out in an integrated manner. BI learning activities in the classroom, students must be trained to use more language to communicate, rather than being required to learn more about language. While the teaching of literature, is intended to improve the ability of students to enjoy, appreciate, and understand literature. Knowledge of literature is only a support in appreciating.